KELUARGA SEBAGAI BASIS PENDIDIKAN PERTAMA DAN UTAMA - Hasbi Wahy (Jurnal Ilmiah Didaktika, 2012)
Family is the first environment experiencing by human being when she or he was born in the world. In further development, it is also becomeas a primary environment to build one’s personality. The early days of one is mostly spent in family. Thus, within the family one undergoes a process of main and foremost education. Any form of family, particularly the parents, either verbally or in action, whether it’s teaching, and exemplary practices applied in the social life of the family, will influence one’s subsequent behavior development. Hence, parents should be able to impart good education and the right to children from the early age, in order the subsequent development of one’s behavior could reflect the sublime personality gives any advantage for himself, religion, family, society, as well as nation.